Field enhancement of electronic conductance at ferroelectric domain walls - Rama K. Vasudevan (Nature Portfolio, 2017)
Understanding the conductivity at the nominally uncharged domain walls in ferroelectrics is still far from complete. Here the authors report an enhanced conduction at domain walls in an ultra-thin (001) BiFeO3 film resulting from the formation of a field-induced meta-stable twisted domain nucleus.